Hematocolpos: Rare but Commonly Missed Cause of Recurrent Pain Abdomen in Children – A Case Report and Review of Literature - Bhattarai, Desh Bhakta; Yadav, Bharat; Gautam, Suprima; Regmi, Pradeep Raj (Journal of Institute of Medicine Nepal, 2025)
Hematocolpos, a rare condition, occurs when menstrual blood or secretory fluid accumulates in the vagina due to vaginal obstruction. It is often caused by various congenital urogenital anomalies. Early diagnosis is crucial to prevent complications such as tubal adhesion, pelvic endometriosis, and infertility. Hematocolpos can present with recurrent abdominal pain in children, which is occasionally missed in the early period of hospital visits. A proper approach to a hematocolpos includes physical examination and imaging findings. Magnetic Resonance Imaging plays a crucial role in diagnosis and guidance for surgical interventions.